Risks to Financial Stability and Monetary Policy: Rules or Discretion? - Barrett, Charles Richard; Kokores, Ioanna T.; Sen, Somnath (Scientific Research, 2017)
We evaluate monetary policy which is conducted in a way that addresses financial stability as an explicit monetary policy objective using a simple game theoretic model analysing the strategic interaction between a central bank and a financial sector. The extant literature in favour of “lean-against-the-wind” (LATW) monetary policy calls for more flexibility and the use of longer policy-horizons. We, therefore, assess monetary policy under discretion and under commitment to an instrument rule. Our analysis supports that rule-based LATW monetary policy outperforms the discretionary equivalent, in terms of controlling inflation, anchoring inflation expectations to the central bank’s inflation target and enhancing financial sector profitability. Under substantial risks to financial stability, we conclude that rule-based LATW monetary policy induces the financial sector to impose more prudence on its operation.
Keywords: Monetary Policy; Central Bank; Financial Stability; Strategic Behaviour